Criminal Law beyond the State: The European Model. Issue 2 (24th February 2013) - Fichera, Massimo
Abstract This article will analyse two models of criminal law beyond the State, which are here termed 'eunomic' and 'dialogic'. It will then focus on one case study, European criminal law, which was inherently 'dialogic' until the last decade of the past century but has now quite unique features. In accordance with classic liberal views, criminal law has always been conceptualised as one of the most salient attributes of the sovereign State. The monopoly on the use of violence was to be legitimised by the State's concern for the sphere of autonomy of the individual. It is submitted in this article that it is precisely this condition that is lacking in the current European model, which promotes security‐oriented paradigms of self‐fulfilment and effectiveness. However, criminal law, if properly conceived, could in theory function as a powerful vehicle of integration.